FICTIONAL CHARACTER AS A BRAND PERSONALITY FOR PROMOTION IN THE INDONESIAN MARKET: A SYSTEMATIC LITERATURE REVIEW - Wildan Guretno Prasetiyo; Ridho Riadi Akbar (Institute of Research and Community Outreach - Petra Christian University, 2025)
The use of fictional characters in promotional campaigns has grown a lot in the last few years. Notable examples include Tomoro Coffee, UNIQLO, and Mobile Legends: Bang Bang, which have successfully incorporated characters from the anime series Jujutsu Kaisen into their marketing strategies. This trend aligns with Indonesia's substantial anime viewer base, which reached approximately 50 million in 2023 and continues to grow proportionally with population expansion. This study aims to explore the potential relationships between a fictional character, brand personality, and promotion via a systematic literature review using PRISMA 2020, analyzing 45 articles from major databases (Web of Science and Google Scholar), drawing on diverse website sources, especially case studies relevant to the Indonesian market. The results show that there are three key links between: (1) a fictional character and a brand's personality, empirical studies show fictional characters boost consumer engagement psychologically; (2) a brand's personality and a promotion, studies confirm human representatives shape marketing strategically; (3) a fictional character and a promotion, research affirms fictional characters' promotional impact. Utilizing a fictional character as a brand personality offers significant potential for product marketing in Indonesia, supported by the country's large anime fanbase. These findings should pave the way for more study into quantitative investigation into the identified relationships and creating the ideal fictional character to use as a brand personality in order to make advertising more effective in Indonesia. The practical implications of this study offer implementable knowledges for brands utilizing anime collaborations to enhance market penetration in Indonesia.